P117 A pilot study of a novel electrode system for brainwave acquisition during sleep: Tripolar Concentric Ring Electrodes. (9th November 2022) - Stuart, N; Manners, J; Scott, H; Lechat, B; Kemps, E; Catcheside, P
Abstract: Introduction: Tri-concentric ring electrodes (TCRE) evaluate current density underlying each electrode rather than a voltage difference between two conventionally placed electroencephalography (EEG) electrodes. TCRE signals are more focal and show improved signal-to-noise with markedly reduced electromyographic interference compared to conventional EEG. This pilot study is the first to evaluate sleep using TCRE and power spectral analysis of TCRE versus conventional EEG emulated (eEEG) recordings obtained from TCRE and the outer rings of paired electrodes. Method: Twenty healthy sleepers (8 men, mean±SD age 27.8±9.6 y) completed a single overnight sleep study with a 9-hr sleep opportunity. Participants were set up for polysomnography recording using TCRE for brain activity (18 sites) and conventional gold-cup electrodes for eye movements, muscle activity, and heart rate. A fast Fourier transform using multitaper-based estimation was applied in 5-s epochs to calculate relative powers in delta, alpha, theta, sigma and beta frequency bands for eEEG and TCRE signals throughout sleep. Results: At the Cz position, TCRE showed greater relative delta power and reduced beta powers across sleep stages compared to eEEG. For example, TCRE had higher delta activity during NREM stage 2 sleep than eEEG (mean [SD]; 89% [5.7] vs 64% [6]) and lower beta activity during wake (3.4% [2] vs 17.3% [7.9]). Ongoing analyses will compare outcomes across electrode locations. Conclusions: Brain activity acquisition via TCRE may reduce artefact interference and potentially identify new markers during sleep that are associated with sleep quality, health, and functioning.